Measurement of Field Sound Transmission Loss of Blockwall Partition Between Two Rooms of a Tower in Jakarta - Maharani Ratna Palupi; Denny Hermawanto (LIPI Press, Anggota IKAPI, 2017)
A field sound transmission loss measurement to obtain the field sound transmission class (FSTC) from partition between spaces on 27th floor Tower